PENGARUH ASSET SPESIFIK DAN KEPEMILIKAN ASING TERHADAP CORPORATE SUSTAINABILITY DENGAN MEDIASI CORPORATE GOVERNANCE - TANGKE, PAULUS; HABBE, ABDUL HAMID (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2017)
This study aims to examine the effect of specific assets and foreign ownership on corporate sustainability with corporate governance as a mediation. This study is an empirical research using secondary data in the form of non-financial company data listed in the Indonesia Stock Exchange period 2011-2015. Based on the results of company sample selection conducted by purposive sampling method, it was selected 132 companies or 660 data years of the company. The theory used in this research is the stakeholders theory as the main theory with the theory of RBV as a supporting theory. The analytical method used in this study is path analysis using multiple regression test statistic tool - SPSS Version 24. The results of this study indicate that specific assets have a positive and significant influence on corporate governance, but have a negative and insignificant effect on corporate sustainability. While foreign ownership has no effect on corporate governance but has negative and significant influence on corporate sustainability. Sobel test shows that Corporate governance in specific asset relation with corporate sustainability in this research is classified as type full mediation, but in foreign ownership relationship with corporate sustainability, corporate governance variable is classified as type no mediation